Neoadjuvant therapy for hepatocellular carcinoma—priming precision innovations to transform HCC treatment - Goodsell, Kristin E.; Tao, Alice J.; Park, James O. (Frontiers in Surgery, 2025)
Hepatocellular carcinoma (HCC) is increasing in prevalence globally, and cure remains limited with non-operative treatment. Surgical intervention, through resection or transplantation, offers a potential for cure for select patients. However, many patients present with advanced or unresectable disease, and recurrence rates remain high. Recent advances in systemic therapies, particularly immune checkpoint inhibitors, have demonstrated promise in treating unresectable HCC and as adjuvant therapy. Evidence from adjuvant trials highlights the synergistic potential of combined liver-directed and systemic therapies. These findings have ignited growing interest in neoadjuvant therapy across various scenarios: (1) as a bridging strategy while awaiting transplantation, (2) for downstaging disease to enable transplantation, (3) for converting unresectable disease to a resectable state, or (4) as neoadjuvant treatment in operable cases. Early-stage trials of neoadjuvant therapy in resectable HCC have reported promising outcomes. To realize the potential of neoadjuvant treatment for HCC, thoughtfully designed, adequately powered, multi-center clinical trials are essential.